Research Project ESPON and INSPIRE Directive as a Tool for Spatial Planning Support - Drzazga, Dominik (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This paper deals with the issue of information's instruments for spatial planning. Spatial planning is a system of public regulation which is use by legal authorities on local, regional, and national level to coordinate human activities such as: investments, mobility, development of settlements, protection of natural areas etc. Planning is going to be an important tool for achieving goals of cohesion policy, however its effectiveness depends on appropriate data and information concerning processes of spatial development. Monitoring of spatial development trends within European Union countries is a main goal of ESPON program (European Observation Network for Territorial Development and Cohesion) which integrate scientific spatial research within European countries. To support decision making process in the field of spatial development, EU established and introduced INSPIRE directive (Infrastructure for Spatial Information in the European Community). Both initiatives are implemented in Poland as a supporting instruments for spatial planning system. In the final part of the article, the most important needs related to provision of information for spatial planning, are underlined.